Palestinians Born in Exile: Diaspora and the Search for a Homeland by Juliane Hammer (Austin: University of Texas Press, 2005. 271 pages.) (American Journal of Islam and Society, 2007)
There is a striking lack of studies on the Palestinian diaspora. Undoubtedlythe pioneering work of Edward Said (“Reflections on Exile,” in Out There:Marginalization and Contemporary Cultures, eds. Russell Ferguson [TheMIT Press: 1990]) on exile and Rashid Khalidi (Palestinian Identity: TheConstruction of Modern National Consciousness [Columbia UniversityPress: 1997]) both touch on many of the related issues of collective memory,cultural identity, and the relationship between the “center” (the homeland)and the diasporic communities and how these issues manifestedthemselves in the Palestinian case. More recently, Abbas Shiblak (Reflectionson Palestinian Diaspora in Europe [2000]), Sari Hanafi (Here andThere: Analyses of the Relationship between Diaspora and the Centre [2001:in Arabic]), and Helena Schulz and Juliane Hammer (The Palestinian Diaspora:Formation of Identities and Politics of Homeland [Routledge: 2003])explore different aspects of the Palestinian diaspora.Juliane Hammer’s new study examines young Palestinian returnees aspart of a larger social, historical, political, and cultural framework (p. 114).She conducted her research in the mid-1990s, a crucial period between twophases: one of peace and hope following the signing of the Declaration ofPrinciples in 1993, and another one that started in 1997 with the deteriorationand breakdown of the peace talks, and, consequently, with the eruption of thesecond Intifada in 2000. For her survey, she chose a sample of two main categoriesof young returnees: those of the Palestinian Authority strata (a`idin)and the children of Palestinian expatriates who live in the West but mainly inthe United States (Amerikans). The interviewees were mainly adolescent oryoung men and women from and around Ramalla and Jerusalem.The return process has been described chronologically, as a series offive steps or stages ranging from the decision to return to plans for the nearfuture. As the study argues, this return entails a process of the returnees’rewriting aspects of their identities. Hammer does not see, however, that thechronological approach is the only way of looking at the process of return.She sees the transformation (what she calls the “rewriting of identities”) alsoby dividing “identity” into different aspects, and then investigating how therespondents remembered these aspects from their childhood and youth in the ...